Electrodepositing Ag on Anodized Stainless Steel for Enhanced Antibacterial Properties and Corrosion Resistance - Yi Shao; Yue Jiang; Yongfeng Wang; Qiangsheng Dong; Cheng Wang; Yan Wang; Feng Xue; Chenglin Chu; Jing Bai (Journal of Functional Biomaterials)
Antibacterial stainless steels have been widely used in biomedicine, food, and water treatment. However, the current antibacterial stainless steels face challenges in balancing corrosion resistance and antibacterial effectiveness, limiting their application range and lifespan. In this study, an oxide layer sealed with antibacterial Ag particles was constructed on the surface of 304 stainless steel through anodizing and electrodeposition, and the process parameters were optimized for achieving long-term antibacterial properties. The electrochemical tests demonstrated that the composite coating effectively enhanced the corrosion resistance of 304 stainless steel. The X-ray photoelectron spectroscopy analysis revealed the close binding mechanism between the Ag particles and the micropores in the oxide layer. Furthermore, the antibacterial stainless steel has an antibacterial rate of 99% against Escherichia coli (E. coli) and good biocompatibility. This study provides an effective approach for designing efficient, stable, and safe antibacterial stainless steel.